2020
DOI: 10.1128/msystems.00605-20
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Success of the Marine Bacterium SAR11 Analyzed through a Metagenomic Perspective

Abstract: The SAR11 clade of Alphaproteobacteria is the most abundant group of planktonic cells in the near-surface epipelagic waters of the ocean, but the mechanisms underlying its exceptional success have not been fully elucidated. Here, we applied a metagenomic approach to explore microdiversity patterns by measuring the accumulation of synonymous and nonsynonymous mutations as well as homologous recombination in populations of SAR11 from different aquatic habitats (marine epipelagic, bathypelagic, and surface freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 84 publications
12
36
0
Order By: Relevance
“…Actinomarinales” species that are made up of discrete populations with an ANIr of ca. 97%, similar to other nonstreamlined genomes ( 27 ), suggesting fewer concurrent species or less interspecies recombination. Another major difference at the level of comparative population genomics between these two streamlined microbes is the size of the core genome, ca.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Actinomarinales” species that are made up of discrete populations with an ANIr of ca. 97%, similar to other nonstreamlined genomes ( 27 ), suggesting fewer concurrent species or less interspecies recombination. Another major difference at the level of comparative population genomics between these two streamlined microbes is the size of the core genome, ca.…”
Section: Discussionsupporting
confidence: 62%
“…4B ). In contrast, Pelagibacterales populations are characterized by ANIr values below 95%, and the threshold in the linear recruitment plots is located above 80% identity, suggesting much higher intrapopulation diversity ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the median dN/dS value was ca. 0.09 for LGC, this value was comparable to the better known marine SAR11 clade (34) and suggests a strong purifying selection acting on the genome evolution of this subclade (Table S3). Within the HGC subclass, we observed much more variable values.…”
Section: Differential Genomic Features Of the Sar116 Subcladessupporting
confidence: 58%
“…These genomic features suggested that members within the LGC subclade are undergoing a streamlining process without genome reduction. For that reason, we studied other characteristic genomic parameters that have been proposed to be relevant in the streamlined genomes such as selective pressure and the number of paralogs (34)(35)(36)(37). Microevolution was measured as the ratio of nonsynonymous to synonymous polymorphisms (dN/dS ratio).…”
Section: Differential Genomic Features Of the Sar116 Subcladesmentioning
confidence: 99%